Mechanisms of Metal Resistance and Homeostasis in Haloarchaea. (21st February 2013) - Srivastava, Pallavee; Kowshik, Meenal
Abstract : Haloarchaea are the predominant microflora of hypersaline econiches such as solar salterns, soda lakes, and estuaries where the salinity ranges from 35 to 400 ppt. Econiches like estuaries and solar crystallizer ponds may contain high concentrations of metals since they serve as ecological sinks for metal pollution and also as effective traps for river borne metals. The availability of metals in these econiches is determined by the type of metal complexes formed and the solubility of the metal species at such high salinity. Haloarchaea have developed specialized mechanisms for the uptake of metals required for various key physiological processes and are not readily available at high salinity, beside evolving resistance mechanisms for metals with high solubility. The present paper seeks to give an overview of the main molecular mechanisms involved in metal tolerance in haloarchaea and focuses on factors such as salinity and metal speciation that affect the bioavailability of metals to haloarchaea. Global transcriptomic analysis during metal stress in these organisms will help in determining the various factors differentially regulated and essential for metal physiology.